The Influence of Financial Literacy and Financial Inclusion on the Performance of MSMEs in Dompu - Yusuf, Moh; Mulyati, Mulyati; Mauzu, Fahrul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the influence of Financial Literacy and Financial Inclusion on the Performance of Micro, Small, and Medium Enterprises (MSMEs) in Dompu Regency. MSMEs are a vital sector in the regional economy, and their performance is affected by the ability to manage finances and access formal financial services. This research adopts a quantitative approach using multiple linear regression analysis. Data were collected from 91 MSME actors through questionnaires and analyzed using SPSS. The results show that Financial Literacy (X1) and Financial Inclusion (X2) have both simultaneous and partial positive and significant effects on MSME Performance (Y). The F-test significance value is 0.000, and the t-tests for variables X1 and X2 also show significance values of 0.000. The coefficient of determination (R²) is 0.671, indicating that 67.1% of the variation in MSME Performance can be explained by the two independent variables. These findings highlight the importance of enhancing financial understanding and access to financial services to improve business growth among MSMEs.